Endovascular extraction of entrapped long-term central feeding catheter: Case series. Issue 3 (May 2019) - Michalak, Marcin; Januszkiewicz, Łukasz; Majstrak, Franciszek; Gawałko, Monika; Opolski, Grzegorz; Grabowski, Marcin
Long-term tunneled central venous catheters are widely used in several clinical indications, that is, hemodialysis, chemotherapy, and total parenteral nutrition. However, central venous catheters are associated with a number of complications, including catheter occlusion and sepsis, which may necessitate earlier catheter removal. In most cases manual traction is sufficient to remove the catheter. Nevertheless, in some cases severe adhesions, formed between the catheter and the vessel wall, complicate simple catheter removal. We present four cases of entrapped long-term central venous catheters and describe methods (e.g. endoluminal balloon dilatation and wire snare) performed by experienced cardiologists at high-volume center to remove them. We claim that permanent central venous catheters removal procedures may be unpredictable and hazardous. Therefore, entrapped central venous catheters should be extracted by experienced operators in specialized high-volume centers.